Productividad del cultivo de fréjol (Phaseolus vulgaris l.), mediante la aplicación foliar de tres dosis de ácidos húmicos en la parroquia del triunfo, cantón La Maná. - Aro Morán, Fabricio Jesús (2023)
The research project was carried out in El Triunfo parish, La Maná cantón - Ecuador where the maximum temperature is 23°, the minimum 17°, and the relative humidity of 86.83% with an annual average rainfall of 3029.30 mm and 735.70 light hours per year. In addition, the soil is formed by substratum and it’s a kind of loamy-sandy soil. The objective was focused on the evaluation of the productivity of the bean (Phaseolus vulgaris l.) crop, through the foliar application of three doses of humic acids. Moreover, to evaluate the agronomic variables of bean (Phaseolus vulgaris l.) with the application of humic acids, so determining the treatment with the best performance in the cultivation of beans (Phaseolus vulgaris l.) in order to carry out the cost-benefit analysis of the study treatments. Finally, the best T4 humic acid dose was obtained while 1.5 ml/L had the greatest efficacy in the studied variables. On the other hand, it was possible to observe that the treatment with the lowest performance was T1 without any relevant variable within the investigation because of its study was for comparison of data. Furthermore, the economic analysis of the best treatment to the application of the different doses of humic acids in relation to T4 humic acids +1.5 ml implies an expense of $7.40 and a yield of $3.42 net profit.